PENGARUH PERILAKU STAF TENTANG PENGOBATAN TERHADAP PENYEMBUHAN LUKA PASCA SEKSIO SESAREA - Enggal Sari Maduratna (NHM PRESS, 2018)
The main problem that must be faced, that is wound healingafter surgery. The staff behavior was one of the factors thatsupport and affect the wound healing process. In reality thereare still mothers with post partum cesarean section woundhealing process not heal the wound base criteria and there aresigns of infection as much as 30%. The purpose of this studywas to analyze the influence of the behavior of the staff aboutthe treatment and healing of wound healing after cesareansection in Syarifah Ambami Rato Ebu Bangkalanhospitals.Design of this study uses analysis with retrospektif approach.The population are 44 people, samples consist of 40 people withsimple random sampling technique. The independent variablebehavior of the staff, the dependent variable of the woundhealing. Collecting data using questionnaires with chi squaretest.The result showed that mostly of data by category caring staffbehavior as much as 24 respondents (60%) and mostly categoryof healed wound healing as much as 24 respondents (60%.Theresult of statistical chi square test from two variables shows thatprobability values > α is 0,018 < 0,05 indicates influencebetween behavior of the staff with the wound healing aftercesarean in Syarifah Ambami Rato Ebu Bangkalan hospitals.Caring staff behavior that can make the patientcomfortable and feel cared. Patients who feel comfortable andcared have a lot bit can affect the healing process. So, Theresearcher expects following up with counseling that he can getinformation about the complaints during experienced the woundhealing process.